Pengembangan Biomagz sebagai Sumber Belajar Biologi Siswa SMA - Trijulensius, Gregorian; Taiyeb, Mushawwir; Azis, Andi Asmawati (Biology Teaching and Learning, 2020)
Abstract. This research was aimed to produce BioMagz product as an alternative resource of independent learning which was valid and practical used in SMA Negeri 1 Mangkutana. This was a research and development using 4D model by Thiagarajan which consisted of 4 steps, namely (1) Define, (2) Design, (3) Develop and Disseminate. The research result developed BioMagz was valid and practical. The value of the validity was 4.17 which meant that BioMagz as an alternative resource of independent learning included in the valid criteria. The value of practicality was 4.6, which meant that BioMagz as an alternative resource of independent learning belonged to the practical criteria. While the student response presentation of 84,5% which means BioMagz got positive response from student. Keywords: BioMagz, Alternative, Resource of Independent Learning